LAPORAN KASUS : PENANGANAN TRANSMISSIBLE VENEREAL TUMOR PADA ANJING LOKAL DI ANOM VET CLINIC - Yohanes T. R. M. R. Simarmata; Margie P. Mila Meha; I Dewa Made Anom (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2020)
Transmissible venereal tumor is a tumor that generally infects male and female genitalia and transmission occurs due to marriage and licking. On August 7th , 2019 the owner came with complaints of fresh blood dripping continuously from the vulva of Unyil, a local dog, female, approximately 3 years old, brown hair color, with a weight of 10.2 kg. After a physical examination in the perineal area, there is a mass like grapes formed in the vagina. Based on the results of physical examination and haematology test, the dog was diagnosed with transmissible venereal tumor. Handling is done in this case by removing the mass such as grapes formed in the vagina through surgery.